The effect of conflict history on cooperation within and between groups: Evidence from a laboratory experiment - Goone Beekman; Stephen L. Cheung; Ian Levely (Charles University in Prague, Institute of Economic Studies (IES), 2015)
We study cooperation within and between groups in the laboratory, comparing treatments in which two groups have previously been (i) in conflict with one another, (ii) in conflict with a different group, or (iii) not previously exposed to conflict. We model conflict using an inter-group Tullock contest, and measure its effects upon cooperation using a multi-level public good game. We demonstrate that conflict increases cooperation within groups, while decreasing cooperation between groups. Moreover, we find that cooperation between groups increases in response to an increase in the efficiency gains from cooperation only when the two groups have not previously interacted.
Keywords: C92; D64; D74; H41; 330; within- and between-group cooperation; inter-group conflict; group identity; multi-level public good experiment; Tullock contest; other-regarding preferences